Don’t Fear the Big Words: An Approach to Scientific Literacy Development in a Cape Breton Middle School - Robertson, Erin K.; Snow, Kathy M. E.; Polegato, Jillian L.; Bereta, Darlene (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
Literacy can have a major impact on comprehension of vocabulary rich content specific areas, such as science. Understanding the vocabulary rich science terminology introduced during the Middle School Years can support conceptual understanding of science and by extension students’ future academic pathways. In our action research project, we worked with a grade eight science teacher along with 75 students to design and test two units of work (Cell and Microscope) when taught using an integrated literacy approach founded upon the inclusion of morphological awareness and the Greek and Latin etymology of scientific vocabulary. Though our quantitative results showed there was little to no difference in students’ unit knowledge or vocabulary scores through the use of this adapted teaching model, the qualitative results provided enough strength for the partner teacher to adopt the integrated approach in all of her future teaching of vocabulary. The teacher noted the new method was particularly useful for engagement of habitual non- participators, and those more reluctant to take risks in the classroom. Therefore, while the new instructional method did not show an immediate increase in test scores, qualitative findings provided strong support that it is critical to deconstructing barriers for learners.